Plasma Levels of IL-17, VEGF, and Adrenomedullin and S-Cone Dysfunction of the Retina in Children and Adolescents without Signs of Retinopathy and with Varied Duration of Diabetes - Semeran, Kornel; Pawłowski, Przemysław; Lisowski, Łukasz; Szczepaniak, Izabela; Wójtowicz, Jerzy; Ławicki, Sławomir; Bakunowicz-Łazarczyk, Alina; Bossowski, Artur (Mediators of Inflammation, 2013)
The study objective was to assess chosen biochemical parameters of blood and bioelectric function of the retina in patients with T1DM. The study group consisted of 41 patients with T1DM with no signs of diabetic retinopathy. The control group included 21 pediatric patients. We performed (1) S-cone ERG testing with retina response stimulation in both eyes at the luminance of 0.1, 0.2, and 0.5 (cd × s/m2) with the 440 nm blue flash and light application of the amber background (300 ph cd/m2, 495 nm wavelength), (2) anthropometric measurements, (3) biochemical investigations: IL-17, VEGF, and ADM by the ELISA method. A comparison of the ERG results with biochemical investigations indicates a likely correlation between the worsening of retinal bioelectric function and VEGF levels growing with diabetes duration. We showed a negative correlation between ADM and HbA1c and described possible causes of ADM reduction observed in subgroup I. We demonstrated the presence of bioelectric retinal dysfunction already before the diagnosis of diabetic retinopathy, which provides new possibilities in the diagnosis of preclinical chronic complications of diabetes. The changes observed in the levels of IL-17, ADM, and VEGF suggest their involvement in the diabetic pathogenesis of eye diseases.